Domain interactions determine the conformational ensemble of the periplasmic chaperone SurA. (31st August 2020) - Marx, Dagan C.; Leblanc, Mathis J.; Plummer, Ashlee M.; Krueger, Susan; Fleming, Karen G.
Abstract: SurA is thought to be the most important periplasmic chaperone for outer membrane protein (OMP) biogenesis. Its structure is composed of a core region and two peptidylprolyl isomerase domains, termed P1 and P2, connected by flexible linkers. As such these three independent folding units are able to adopt a number of distinct spatial positions with respect to each other. The conformational dynamics of these domains are thought to be functionally important yet are largely unresolved. Here we address this question of the conformational ensemble using sedimentation equilibrium, small‐angle neutron scattering, and folding titrations. This combination of orthogonal methods converges on a SurA population that is monomeric at physiological concentrations. The conformation that dominates this population has the P1 and core domains docked to one another, for example, "P1‐closed" and the P2 domain extended in solution. We discovered that the distribution of domain orientations is defined by modest and favorable interactions between the core domain and either the P1 or the P2 domains. These two peptidylprolyl domains compete with each other for core‐binding but are thermodynamically uncoupled. This arrangement implies two novel insights. Firstly, an open conformation must exist to facilitate P1 and P2 exchange on the core, indicating that the open client‐binding conformation is populated at low levels even in the absence of client unfolded OMPs. Secondly, competition between P1 and P2 binding paradoxically occludes the client binding site on the core, which may serve to preserve the reservoir of binding‐competent apo‐SurA in the periplasm.